Every sponge its own name: removing Porifera homonyms - van Soest, Rob W.m.; Hooper, John N.a.; Butler, Peter J. (Zootaxa, 2020)
The occurrence of different sponge species bearing the same Linnean binomial name combination, i.e. homonyms, is to be avoided for obvious reasons. In a review of sponge taxon names of the World Porifera Database, we detected 121 homonymic cases (115 species-group names, 6 genus-group names), involving a total of 272 nominal taxa. It is the object of the present study to remove their occurrence by proposing new names for the junior homonyms following the rules of the International Commission of Zoological Nomenclature as laid down in the Code (ICZN, 1999) and the on-line edition http://iczn.org/iczn/index.jsp . Homonym cases are discussed and, where applicable, junior homonyms are either replaced by nomina nova or reassigned to their earliest available synonyms. The order in which the homonyms are treated is alphabetical on original species name, with genus names separately treated at the end. A summary table with all proposed name changes is also presented to allow quick access to the junior homonyms and their proposed new names. A total of 116 nomina nova are proposed, including five new genus names.